In vitro ruminal fermentation of low-quality forages as influenced by the treatment with exogenous fibrolytic enzymes - Giraldo L.A.; Carro M.D.; Ranilla M.J.; Tejido M.L.; Mohamed A.H. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The effects of three fibrolytic enzymes on the in vitro ruminal fermentation of five low-quality forages (three cereal straws (barley, wheat and rice), corn stover and grass hay) were investigated using batch cultures of mixed ruminal microorganisms. Four different treatments were investigated: no additive (control; CON), cellulase from Aspergillus niger (CEL; Fluka Chemie GmbH), xylanase from ruminal microorganisms (XYL; Megazyme International Ireland Ltd), and a 1:1 mixture cellulase:xylanase (MIX). Enzymes (20 IU/g forage dry matter (DM)) were applied directly onto the forages 24 h before incubation with buffered ruminal fluid at 39ºC for 24 h. The treatment with CEL increased (P<0.05) gas production after 24 h of incubation for wheat straw, barley straw and grass hay, whereas the treatment with MIX and XYL did not affect (P>0.05) gas production for any forage. For all substrates, neutral-detergent fibre digestibility (NDFD) and NH3-N concentration were not affected (P>0.05) by the addition of enzymes. The treatment of forages with CEL increased the production of propionate for grass hay, corn stover and barley straw, and increased (P<0.05) total VFA production for wheat straw and corn stover. No effects (P>0.05) of MIX and XYL treatments on VFA production were observed for any substrate. The results indicate that the pre-treatment of low-quality forages with fibrolytic enzymes under the conditions of the present experiment contributed little, if any, to ruminal fibrolytic activity.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)